Career dynamics and gender gaps among employees in the microfinance sector - Ina Ganguli; Ricardo Hausmann; Martina Viarengo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
While microfinance institutions (MFIs) are increasingly important as employers in the developing world, there is little micro-level evidence on gender differences among MFI employees and MFIs' relation to economic development. We use a unique panel dataset of employees from Latin America's largest MFI to show that gender gaps favouring men for promotion exist primarily in the sales division, while there is a significant gender wage gap in the administrative division. Among loan officers in the sales division, the gender gap in promotion and wages reverses. Finally, female employees tend to work with clients with better loan terms and a history of loans with the institution.
Keywords: J16; J62; M51; O1; 330; gender gaps; job mobility; promotion; microfinance; economic development; panel data analysis